Aplikasi Fuzzy Analytical Hierarchy Process untuk Menentukan Prioritas Pelanggan Berkunjung Ke Gerai Minuman Choco Late - Rahmawati Rahmawati; Anneke De Resta; Ade Novia Rahma; Zukrianto Zukrianto; Wartono Wartono (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2022)
Choco Late is a beverage outlet in Panam Pekanbaru that sells drinks with various flavors that can be combined with various additional toppings. This study aims to determine the priority criteria for customers visiting the Choco Late beverage outlet using the Fuzzy AHP method. The AHP Fuzzy method combines the AHP method and the Fuzzy method. The AHP Fuzzy approach, especially the triangular fuzzy number approach with the AHP scale, must be able to minimize uncertainty so that the results are accurate. The criteria used in this study are service, goods sold, and the Choco Late environment. Based on the data calculation steps obtained by Fuzzy AHP, the respondent has a CR value = 0.0834, which means it is consistent because it meets the standards set CR < 0.10, and the main priority is service with a criterion weight of 0.7339